Field margins enhance weed seed predation in adjacent fields in early spring - Petit, Sandrine; Carbonne, Benjamin; Etcheverria, Zoé; Colbach, Nathalie; Bohan, David Andrew (Frontiers in Agronomy, 2023)
Seed depletion by granivorous organisms can regulate weeds in arable agriculture. Enhancing this regulation can be achieved by adopting farming practices that favour seed predators. Here, we test the hypothesis that the presence of grassy field margins along field edges will increase in-field weed seed predation, in comparison to situations where no grassy field margin is present. Predation cards with Poa annua were exposed in 15 wheat fields in May and June 2018 along 57 transects at distances of 4, 8, 16, 32 meters from the field edge. Cards were either caged (predation by invertebrates) or uncaged predation byall seed predators). We found that in May, the presence of grassy field margins led to higher in-field predation rates at all distances from the field edge, with a very high contribution of invertebrates to seed predation. In June, the presence of grass margin had no impact on in-field seed predation, to which invertebrates and vertebrates contributed equally. This preliminary study provides some support to the hypothesis that grassy field margins augment in-field weed seed predation in early spring. It is plausible that these habitats are emergence sites for invertebrates, with a subsequent high abundance of adults nearby grass margins in early spring, before they disperse more widely across fields and/or switch to alternative prey. These results call for further comparative research on the impact of grass margins on seed predation, seed predators and alternative prey during the whole cropping season.